(untitled) (Research, Society and Development, 2025)
Introduction: Human Papillomavirus (HPV) is a sexually transmitted infection affecting approximately 54.4% of sexually active women in Brazil and is the leading cause of cervical and anal cancer, responsible for over 90% of these cases. HPV is classified into low-risk types, which cause benign lesions, and high-risk types, associated with neoplasms. Detection is performed via cytology or molecular techniques such as Polymerase Chain Reaction (PCR). There are over 200 HPV types, with types 16 and 18 being the most oncogenic. Vaccination is the main preventive measure, and the quadrivalent vaccine, available through the Brazilian Public Health System (SUS) since 2014, protects against types 6, 11, 16, and 18, showing high efficacy in preventing precancerous lesions and invasive cancer. Cervical cancer remains a significant public health issue, with over 600,000 new cases and 340,000 deaths annually in Brazil. Objective: To analyze PCR-positive HPV test data from 2023–2024 and relate it to vaccination coverage, aiming to improve prevention and eradication strategies for cervical cancer in Brazil. Results: The most prevalent genotypes were HPV 53, 52, and 54, which are not covered by the quadrivalent vaccine. Conclusion: Broader studies are needed to identify potential gaps in national vaccine coverage and, if confirmed, to implement more effective public health policies to protect the female population.